2003
DOI: 10.1039/b306778e
|View full text |Cite
|
Sign up to set email alerts
|

New ligand bearing preorganized binding side-arms interacting with ammonium cations: Synthesis, conformational studies and crystal structureElectronic supplementary information (ESI) available: molecular modeling studies. See http://www.rsc.org/suppdata/nj/b3/b306778e/

Abstract: The synthesis and characterization of the new tetraazamacrocycle 4-(N),10-(N)-bis[2-(3-hydroxy-2-oxo-2Hpyridin-1-yl)acetamido]-1,7-dimethyl-1,4,7,10-tetraazacyclododecane (L) is reported. L shows two 3-(hydroxy)-1-(carbonylmethylen)-2(1H)-pyridinone moieties as side-arms of a tetra-aza-macrocyclic base. The key coupling of side-arms was studied and the most significant results were obtained by activating the 3-(benzyloxy)-1-(carboxymethyl)-2(1H)-pyridinone as pentafluorophenol ester. The acid-base properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Very few polyaza macrocycles bearing HOPO coordinating groups have been described [48,[51][52][53][54]. Macrocycles offer the potential to fine tune the metal chelating properties by varying the cycle's size and fexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Very few polyaza macrocycles bearing HOPO coordinating groups have been described [48,[51][52][53][54]. Macrocycles offer the potential to fine tune the metal chelating properties by varying the cycle's size and fexibility.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the carbonyl oxygen is good hydrogen bonding acceptor for alkyl ammonium protons. 28,29 Therefore, it was envisaged that both compounds might complex salts 3-5 ( Figure 2) in chloroform through intermolecular hydrogen bonding. Before the complexing behaviour was investigated, we first explored the possibility of strong acid-tuned conformational shifting.…”
Section: Resultsmentioning
confidence: 99%
“…2). 19 The fluorescence emission spectra of the Ga(III)/L system, recorded under the experimental conditions used for the kinetic measurements, revealed greater modifications than those of the free ligand. In fact, exciting at 301 nm the fluorophore shows an enhancement of the fluorescence (CHEF) for the Ga(III)/L system together with a slight decrease in the k em , which is at 361 nm in the presence of Ga 3+ instead of 369 nm in the absence of the metal ion (see Fig.…”
Section: Spectrophotometric Experimentsmentioning
confidence: 95%
“…The two HPO moieties have been driven to cooperate by the macrocyclic skeleton in binding guests. 19 The preorganization of the side-arms leads to the formation of an electron rich structure formed by the four converging oxygen atoms and thus suitable to bind hard metal cations.…”
Section: Introductionmentioning
confidence: 99%